Effects of scribing wheel dimensions on LCD glass cutting - Amin, A. K. M. Nurul; Chong , Chee; -, Sayedatul Akma (IIUM Press, 2011)
Nowadays, LCD is present everywhere in man-machine interfaces. It is used on various kind of instrument, such as Personal Digital Assistant (PDA), mobile phone, digital clock due to the superiority of display quality, relatively lower power consumption, small size, low weight, and also to its dimensional flexibility from less than one inch to as large as forty inch diagonal in flat television screen currently, Funaki [1]. Glass cutting is one of the important processes in LCD manufacturing. It has significant impact on the manufacturing yield. In the actual glass cutting process in LCD manufacturing plant, faulty cutting, which is commonly called “misbreaking”, always happens. It is a serious problem that reduces LCD production yield. In 1947, Taylor [2] studied the crack mechanism of glass by point indentation through the making of first Vickers hardness measurement. He observed some cracks at corners of diagonals impression. Holland and Turner [3] investigated strength degradation by scratching with worn and new diamond chips. They found that scratching creates two types of cracks, median and lateral. However, they did not correlate these cracks to material strength. John and Blair [4] conducted similar experiments to investigate the influence of interval time between scratching and breaking on strength. They found that the required breaking load was increased when the interval time was long Muir [5] explained that there are 28 parameters in the scribing process that need to be considered in meeting the quality requirement of glass cutting. Laser splitting of glass has been demonstrated to be effective and economical. Swain [6] discovered that laser splitting of glass necessitates the development of a sub-microscopic crack within the body of the glass by controlling the generation of stress. Veldkamp et al [7] observed cracking during the scratching of several brittle materials including glass. They reported the creation of several types of cracks such as median crack, lateral crack and surface cracks as a function of scratching load or speed. This present work focus on the study of the crack creation and propagation mechanism when apply scribe/break method on ITO coated soda lime glass using Tungsten Carbide scribing wheel. Focus is put at improvement of LCD glass cutting quality and its economic value.